2011
DOI: 10.2114/jpa2.30.179
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamical System Analysis of the Development of Spontaneous Lower Extremity Movements in Newborn and Young Infants

Abstract: This study's aim was to evaluate the characteristics of newborn and young infants' spontaneous lower extremity movements by using dynamical systems analysis. Participants were 8 healthy full-term newborn infants (3 boys, 5 girls, mean birth weight and gestational age were 3070.6 g and 39 weeks). A tri-axial accelerometer measured limb movement acceleration in 3-dimensional space. Movement acceleration signals were recorded during 200 s from just below the ankle when the infant was in an active alert state and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 19 publications
(19 reference statements)
2
20
0
Order By: Relevance
“…Interesting, infants with TD showed both linear and quadratic developmental patterns on their reaching behaviors. These findings support our original hypothesis because showing inverted, U-shaped trajectories during the developmental process is common in typical developing infant population (Gima et al, 2011). In our study, the quadratic curves of reaching number and hand-toy contact duration indicated that part of reaching behaviors were an inverted U-shaped trajectory with the highest performance between 2-to 7-months of age in infants with TD.…”
Section: Discussionsupporting
confidence: 90%
“…Interesting, infants with TD showed both linear and quadratic developmental patterns on their reaching behaviors. These findings support our original hypothesis because showing inverted, U-shaped trajectories during the developmental process is common in typical developing infant population (Gima et al, 2011). In our study, the quadratic curves of reaching number and hand-toy contact duration indicated that part of reaching behaviors were an inverted U-shaped trajectory with the highest performance between 2-to 7-months of age in infants with TD.…”
Section: Discussionsupporting
confidence: 90%
“…Hirotaka Gima et al [22] proposed a low-cost system based on accelerometers to evaluate a newborn’s movement.…”
Section: Discussionmentioning
confidence: 99%
“…13,20 COP movement is assessed based on the pressure imprint data, which are sampled with 30 Hz. First, pressure imprint data are pre-processed with bias and superposed noise removal methods.…”
Section: Cop Movement Parametersmentioning
confidence: 99%